IJRBAT 2014
DOI: 10.29369/ijrbat.2014.02.ii.0043
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Behavior of Arundo Donax L.

Abstract: The paper deals with the reproductive investigations of Arundo donax L. The anther wall development conforms to the Monocot type. Male sterility is related to the abnormal behavior of tapetum. The ovules are bitegmic, campylotropous, tenuicellate, feeble tendency towards pseudo-crassi nucellate. Polygonum types of embryo sac with antipodal complex are noticed.The degenerating zygote has been noticed in the embryo sac indicating that after fertilization further development of the embryo are restricted. Hence se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The sterile seeds of the plant may be due to the inability of megaspore mother cells to perform cellular division. It is suggested that the reason for A. donax seeds sterility can be rooted in alterations in gametogenesis, fertilization and post-fertilization (Nikhade & Makde, 2014).…”
Section: Reproductive Behavior and Phenologymentioning
confidence: 99%
See 1 more Smart Citation
“…The sterile seeds of the plant may be due to the inability of megaspore mother cells to perform cellular division. It is suggested that the reason for A. donax seeds sterility can be rooted in alterations in gametogenesis, fertilization and post-fertilization (Nikhade & Makde, 2014).…”
Section: Reproductive Behavior and Phenologymentioning
confidence: 99%
“…One could argue that seedless reproduction is not enough to interprete the ability of populations to swiftly invade new habitats. Despite the previous efforts to fathom this issue through genetic studies (Ahmad et al, 2008;Guarino et al, 2019) and developmental dynamics of A. donax seeds (Nikhade & Makde, 2014), we believe there is still much room for further research to fully understand the reproductive behavior of giant reed.…”
Section: Introductionmentioning
confidence: 96%
“…Because of its vast economic value, giant reed is widely planted in subtropical regions of the world, such as Southern Europe, North Africa, Australia, and America (Guo and Miao, 2010). Giant reed does not produce seed in many areas because the further development of the embryo is restricted (Balogh et al, 2012;Nikhade and Makde, 2014;Alshaal et al, 2015). The propagation of giant reed can be divided into rhizomes or stem cuttings and in vitro biotechnology methods.…”
Section: Origin and Reproduction Of Giant Reedmentioning
confidence: 99%
“…Meiosis occurs in less than 10% of microsporocytes, and no formation of exine occurs in the microsporangium [11]. A. donax sterility has been reported to be related to alterations in gametogenesis and fertilization and post-fertilization development [16]. A. donax sterility most likely has various causes that have led to its agamic propagation strategy.…”
Section: Introductionmentioning
confidence: 99%